Retrospective analysis of rituximab therapy and splenectomy in childhood chronic and refractory immune thrombocytopenic purpura. Issue 4 (June 2016) - Ay, Yilmaz; Karapinar, Tuba H.; Oymak, Yesim; Toret, Ersin; Demirag, Bengu; Ince, Dilek; Ozcan, Esin; Moueminoglou, Nergial; Koker, Sultan A.; Vergin, Canan
Abstract : Immune thrombocytopenic purpura (ITP) results from accelerated platelet destruction mediated by autoantibodies to platelet glycoproteins. Some patients with chronic ITP are refractory to all therapies [steroids, intravenous immunoglobulin (IVIG), anti-D and immunosuppresive drugs] and have chronic low platelet counts and episodic bleeding. We retrospectively evaluated the efficacy and safety of rituximab treatment and splenectomy in paediatric patients diagnosed with chronic and refractory ITP who were unresponsive to steroids, IVIG, cyclosporine and mycophenolate mofetil. Records of patients with chronic and refractory ITP in 459 patients with primary ITP who were followed up in our hospital from January 2005 to December 2014 were reviewed. Fifteen of patients received rituximab and/or applied splenectomy. Fifteen chronic ITP patients (10 boys, five girls) with a mean age of 10 years were enrolled in the study. Two of these patients were suffering from Evans syndrome. The median time since diagnosis of ITP was 10 years. The median follow-up duration after starting Rituximab and splenectomy were 13 and 9.5 months, respectively. None of the seven patients who were treated with rituximab achieved a response. A splenectomy was performed in six of the seven patients who had been treated with rituximab. Complete and partial responses were achieved in 67 and 33% of the patients, respectively. We evaluated the clinical characteristics and responses of chronic ITP patients who did not receive rituximab therapy and underwent a splenectomy. The success rate was 100% in the eight patients with chronic and refractory ITP. Rituximab therapy might not be beneficial for some children with severe chronic ITP who are refractory to standard agents. A splenectomy might be useful and preferable to rituximab.